The Influence of Product Quality and Price Towards Loyalty with Customer Satisfaction as a Mediator: (Survei an Consumers of Jogger Pants in Kenszolla) - Ihza Pratama, Raynaldi; Jatmiko, Rohmat Dwi; Praharjo, Ardik (University of Muhammadiyah Malang, 2023)
This study aims to examine the effect of product quality and price on customer loyalty and satisfaction as a mediator in studies on jogger pants consumers in Kenszolla. This data was obtained through an online survey using a Google form on 384 respondents using a purposive sampling technique on consumers of Kenszolla Jogger Pants. Path analysis shows that product quality has a positive and significant effect on customer loyalty, perceived price suitability has a positive and significant effect on customer loyalty, product quality has a positive and significant effect on customer satisfaction, perceived price suitability has a positive and significant effect on customer satisfaction, customer satisfaction has a positive effect and significant to customer loyalty. The Sobel test shows that customer satisfaction can mediate product quality on customer loyalty, and customer satisfaction can mediate price on customer loyalty.